1 .If a = -8, b = -7, c = 6, verify that (a + b) + c = a +(b + c).
2.If a = -9 and b = -6, show that (a - b) = (b - a).
Answers
Answered by
2
Answer:
Step-by-step explanation:
1. Given - a= -8, b = -7, c = 6
To verify - (a + b) + c = a + (b + c)
Verification - First substitute the values
(-8 + -7) + 6 = -8 + (-7 + 6)
-15 + 6 = -8 - 1
-9 = -9
Therefore, (a + b) + c = a + (b + c)
2. 1. Given - a= -9, b = -6
To verify - (a - b) = (b - a)
Verification - First substitute the values
(-9 - (-6)) = (-6 - (-9))
-3 = 3
Therefore, (a - b) (b - a)
Mark me as brainliest
Similar questions